THE MAIN CAUSES OF TOOTHACHE AND HOME REMEDIES FOR RELIEF - Abduraxmonova, Shohista (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
This article explores the most common causes of toothache and discusses practical methods for providing relief at home before professional dental care is obtained. Tooth pain is one of the most frequent complaints in dentistry and may result from various conditions such as dental caries, pulpitis, periodontal disease, trauma, or sinus-related problems. Understanding the origin of pain is essential for appropriate management. The paper outlines the physiological mechanisms of tooth pain, the risk factors contributing to its occurrence, and safe home-based measures that can temporarily reduce discomfort. It emphasizes the importance of avoiding harmful self-treatment practices and encourages early dental consultation to prevent complications.